Exposure times for colour discrimination in the parafoveal field: a new procedure to detect subtle visual dysfunction in multiple sclerosis patients. Issue 4 (April 1986) - Menabue, R; Nichelli, P; Bellei, S
Abstract : A new procedure to test colour discrimination in the parafoveal field is described. This method was used on 25 healthy controls and 25 subjects having a definite clinical or laboratory-supported diagnosis of multiple sclerosis, with or without a previous history of optic neuritis. The test proved to be sensitive in detecting visual dysfunction even in some patients in whom the standard technique of pattern-reversal evoked potential recordings yielded a normal result.